CO2 absorption using biogas slurry: Recovery of absorption performance through CO2 vacuum regeneration. (March 2017) - He, Qingyao; Xi, Jiang; Wang, Wenchao; Meng, Liang; Yan, Shuiping; Zhang, Yanlin
Highlights: RBS may be a renewable CO2 absorbent for reducing energy consumption. E a value of CO2 regeneration from RBS at 20 kPa and 35–75 °C is 57.78 kJ/mol. CO2 reabsorption capacity of RegBS can be improved by about 318.33%. Lower phytotoxicity can be achieved for CO2 -rich RegBS compared with RBS. CO2 stripping is most effective at 77 °C and 40 kPa. Abstract: As a by-product of anaerobic biogas digestion using biomass as the substrates, raw biogas slurry (RBS) may be a renewable CO2 solvent to capture CO2 and fix CO2 into the crops/plants by forming organic carbon through carbon concentration mechanism (CCM). However its CO2 absorption performance should be enhanced greatly without deteriorating its inherent low phytotoxicity. Recovery and enhancement of CO2 absorption performance of RBS with initial total ammonia nitrogen (TAN) concentration (∼0.152 mol-N/L) was investigated through stripping CO2 saturated in RBS during anaerobic digestion by vacuum regeneration technology. Additionally, phytotoxicity of the regenerated RBS (RegBS) after CO2 reabsorption was also evaluated in terms of EC50 value which represents the CO2 -rich RegBS application concentration causing 50% inhibition to root elongation of mungbean seeds. Results showed that vacuum regeneration technology is a time-effective method to regenerate CO2 from RBS. And the activation energy of CO2 regeneration from RBS under 20 kPa and 35–75 °C is about 57.78 kJ/mol. The main mechanism of CO2 regeneration from RBS may be the decomposition of ammonium bicarbonate. CO2 reabsorption capacity of RegBS is enhanced up to 0.125 mol/L at 77 °C and 40 kPa, which is approximately 3.18-fold higher than that of RBS. If RBS with high TAN concentration can be adopted, much higher CO2 reabsorption capacity may be achieved. CO2 -rich RegBS can obtain the higher EC50 value than RBS, indicating higher application concentrations in agriculture/horticulture, and hence lower phytotoxicities to crops and plants. The maximum EC50 value with 168.8 mL/L can be achieved when using the CO2 -rich RegBS obtained at 47 °C and 10 kPa. 77 °C and 40 kPa may be the optimum conditions to recover CO2 absorption performance of RBS in terms of higher CO2 reabsorption performance and lower phytoxicity of CO2 -rich RegBS.